Application of chloroplast genome in the identification of Phyllanthus urinaria and its common adulterants - Fang, Hui; Dai, Guona; Liao, Binbin; Zhou, Ping; Liu, Yinglin (Frontiers in Plant Science, 2023)
Phyllanthus urinaria L. is extensively used as ethnopharmacological material in China. In the local marketplace, this medicine can be accidentally contaminated, deliberately substituted, or mixed with other related species. The contaminants in herbal products are a threat to consumer safety. Due to the scarcity of genetic information on Phyllanthus plants, more molecular markers are needed to avoid misidentification. In this study, the complete chloroplast (cp) genome of nine species of the genus Phyllanthus was de novo assembled and characterized. The results revealed that all of these species exhibited a conserved quadripartite structure, which includes a large single copy (LSC) region and small single copy (SSC) region, and two copies of inverted repeat regions (IRa and IRb), which separate the LSC and SSC regions. And the genome structure, codon usage, and repeat sequences were highly conserved and showed similarities among the nine species. Three highly variable regions (trnS-GCU-trnG-UCC, trnT-UGU-trnL-UAA, and petA-psbJ) might be helpful as potential molecular markers for identifying P. urinaria and its contaminants. In addition, the molecular clock analysis results showed that the divergence time of the genus Phyllanthus might occur at ~ 48.72 Ma. This study provides valuable information for further species identification, evolution, and phylogenetic research of Phyllanthus.